PENGARUH PENAMBAHAN BUBUK DAUN KELOR TERHADAP KUALITAS ORGANOLEPTIK NUGGET IKAN BELANG KUNING (Ceasio cuning) - Anita Trisia Dimu Lobo; Hemy R. Djasibani; Maria Nahak; Alfionita Atakkari (Politeknik Pertanian Negeri Kupang, 2023)
This research aims to determine the effect of adding Moringa leaf powder on the organoleptic quality of fish nuggets prepared from yellow-striped fish. The data obtained (texture, aroma, and taste) has been analyzed using Analysis of Variance (Anova) and followed by Duncan's Multiple Range Test. The results showed that the addition of Moringa Leaf Powder to the texture evaluation of Yellow Striped fish nuggets had the highest average value 3.46 (in treatment C) and the lowest value was 1.53 (in treatment D) . For the aroma preferences, the highest value was in treatment (3.61) and the lowest value was in treatment D with an average of (1.68), while for taste evaluation the highest value was 3.66 recorded in treatment C and the lowest value was in treatment D with an average value of ( 1.73).Key Words: nuggets, the effect of addition, moringa leaf powder and striped fish yellow.